The effectiveness of measures aimed at improving the skills of employees of the state financial control - Kazakov, Alexander Sergeevich; Prodanova, Natalia Alekseevna; Arhipovskaya, Elena Petrovna; Protasova, Sofya Sergeevna; Kosnikov, Sergey Nikolaevich (Linguistics and Culture Review, 2021)
The article discusses the problems and prospects of professional development of civil servants in the field of internal and external state financial control. The relevance of the research problem is due to the active development of legislation in the field of control and supervisory activities, which leads to increased requirements for state auditors. Since Federal Law No. 79-FL of 27.07.2004 "On the State Civil Service" and the Decrees of the President of Russia adopted in addition to it establish a minimum list of requirements for the qualifications of employees. In practice, the control bodies proceed from a fairly broad interpretation of the qualifications and competence of auditors, which negatively affects the quality of their activities. According to the results of the study, the concept of professional competence of the state auditor was formulated, which should be fixed in the industry legislation, and the Federal Professional Standard of Higher Education in the field of state audit was also studied, in accordance with which employee retraining programs should be brought in order. The material of the article is based on the current legislative framework and taking into account the latest trends in the training of employees of state financial control bodies.